Pengaruh Kepemimpinan Transformasional dan Budaya organisasi Terhadap Kinerja Karyawan( Studi Kasus Di Puskesmas Randulawang) - SUGINO, SUGINO (FEBI IAI Al Muhammad Cepu, 2024)
The purpose of this study was to determine and analyze the effect of transformational leadership on employee performance at Puskesmas Randulawang , to determine and analyze the influence of organizational culture on employee performance at Puskesmas Randulawang and to determine and analyze the influence of transformational leadership and organizational culture. on employee performance at Puskesmas Randulawang The population of this study were all 60 permanent employees of Puskesmas Randulawang . The data analysis technique used is multiple regression. The results of this study indicate that partially transformational leadership and organizational culture have a positive and significant effect on the performance of employees of Puskesmas Randulawang and that transformational leadership and organizational culture simultaneously have a positive and significant effect on the performance of employees of Puskesmas Randulawang.